PENGARUH FUNGISIDA METALAKSIL-M TERHADAP KETERJADIAN PENYAKIT BULAI DAN PRODUKSI POPULASI JAGUNG LAGALIGO X TOM THUMB - Utomo, Setyo Dwi; Islamika, Nur; Dirmawati, Suskandini Ratih; Ginting, Cipta (JURNAL AGROTROPIKA, 2010)
The objective of this study was to evaluate the effect of the application of Metalaksil-M on the disease incidence of downy mildew (Peronosclerospora maydis) and the yield of early-maturing corn genotype LL/TT-1. The experiment was arranged in randomized complete block design with three replications. Treatments consisted of Metalaxyll-M (300 ml in 1000 ml water) applied to the seeds (soaked for 1 minute), applied by spraying to the plants 7 days after planting, and the control. The results showed that the genotype LL/TT-1 was not resistant to downy mildew. The dry weight of ear and seeds per 12 plants harvested from plants were 70 and 72% higher than those of control respectively. The dry weight of ear and seeds per 12 plants harvested from plants sprayed with Metalaxil-M were also significantly higher than those of control.Key words: Peronosclerospora maydis, metalaxyl, seed treatment, Zea mays L.